Clinicopathologic and Prognostic Differences between Three Different Age Groups (Child/Adolescent, Young Adults, and Adults) of Colorectal Cancer Patients: A Multicentre Study - Kaplan, Muhammet Ali; Ozaydin, Sukru; Yerlikaya, Halis; Karaagac, Mustafa; Gumus, Mahmut; Cil, Timucin; Isikdogan, Abdurrahman (Karger, 2019)
Background: Colorectal cancer (CRC) is a rare disease amongst children and adolescents. Previous studies have reported a number of differences between children/adolescents, young adults, and adult patients with CRC. However, none of these studies compared these age groups according to their clinicopathologic and prognostic characteristics. In the current study, we compare these three age groups. Methods:A total of 173 (1.1% of 15,654 patients) young CRC patients (<= 25 years) were included in the study. As a control group, 237 adult CRC patients (>25 years) were also included. Patients were divided into three age groups: child/adolescent (10-19 years), young adult (20-25 years), and adult (>25 years). Results: Statistical differences amongst the three groups in terms of gender (p = 0.446), family history (p = 0.578), symptoms of presentation (p = 0.306), and interval between initiation of symptoms and diagnosis (p = 0.710) could not be demonstrated. Whilst abdominal pain (p < 0.001) and vomiting (p = 0.002) were less common in young adults than in other groups, rectal bleeding and changes in bowel habits were relatively less common in adolescents than in other groups. Rectal localisation (p = 0.035), mucinous adenocarcinoma (p < 0.001), and a poorly differentiated histologic subtype (p < 0.001) were less common in the adult group than in other groups. The percentage of patients with metastasis and sites of metastasis (e.g., peritoneum and lung) differed between groups. The median overall survival was 32.6 months in the adolescent group, 57.8 months in the young adult group and was not reached in the adult group (p = 0.022). The median event-free survival of the adolescent, young adult, and adult groups was 29.0, 29.9, and 61.6 months, respectively (p = 0.003). Conclusions: CRC patients of different age groups present different clinicopathologic and prognostic characteristics. Clinicians should be aware of and manage the disease according to these differences.
Keywords: Colorectal cancer; Young; Adolescent; Child